POPULATION GROWTH AND SUSTAINABLE DEVELOPMENT IN ALGERIA IN LIGHT OF ACHIEVING SOCIAL NEEDS (PROJECTIVE STUDY OF THE PROSPECTS FOR THE YEAR 2050 USING THE SPECTRUM PROGRAM) - Rima Merrad,; Karima Fouded, (International Journal of Innovative Technologies in Social Science, 2025)
The relationship between population and sustainable development represents one of the most urgent and complex issues of the 21st century, Population dynamics and their impacts on natural resources, ecosystems and economic and social systems form a close relationship between the population in any society and the need for services in various fields, The total population size plays the largest role in determining the framework necessary for the community's various service needs.In this context Algeria has been striving since independence to this day to implement developmental strategies that align with the population in order to achieve the greatest possible development to improve their situation in various fields, It has mobilized all its capabilities and resources to meet the needs of the population, particularly in terms of food, education, employment, and living standards. Therefore, the aim of our study is to estimate the basic needs required for the population in terms of food, education, and work, taking into account future demographic changes until the year 2050 in the context of achieving sustainable development.